Design and fabricate portable tower for TV arial - Mohd U'Kasyah, Hashim (2008)
Nowadays, media is very important because its' role as a medium for us to get information especially to know current issues which we can get it from television, radio, newspaper and other relating component. According to the survey and some simple research we can conclude that the most needed medium to get information for people is television because of the modernisation even though internet have more exposed to hem sapiens. Furthermore television can be get in lower price than other instrument. Although this magic box everybody can get it but not all area of community can get clear signal for certain channel especially people who live far from town. For those Who can afford, they can use ASTRO to solve this problem, but try to think for a while to others who cannot afford it? They only use local indoor or outdoor area network to get the better signal. Although outdoor local area perhaps helping, but if there any unexpected problem especially relate to environmental disease it will harm the users. Besides for using this local area we need to place it on top and people who are not know about safety will not alert for any caution and the risk to get injured Is higher. It is also hard when to outer the area position to get the signal. This problem has being encountered for a long time, so the processing engineers have study for this case. They do some research and develop new idea about the local area model and also the placement to that area. This idea has help me to decorated new area placement which has safety model and ergonomic characteristics that will increase the safety to the users. So, my project idea has being base on this research to help our community to get better signal to watch television and live in a better conditions.